Implementasi Gaya Kepemimpinan Religius-Humanis Kepala Madrasah dalam Membentuk Karakter Positif Siswa di Sekolah - Lalu Muhammad Wiresentana; Edi Muhammad Jayadi; Muhammad Muhammad (Ulul Albab: Majalah Universitas Muhammadiyah Mataram, 2026)
Research on the religious-humanistic leadership of madrasah principals is important because strengthening students’ character education requires a leadership approach that focuses not only on administrative aspects but also on religious and humanistic values. This study aims to analyze the implementation of religious-humanistic leadership styles by madrasah principals in shaping students’ positive character at school. The study employs a qualitative approach using the Systematic Literature Review (SLR) method. Literature sources were obtained from the indexed databases Scopus, DOAJ, and Google Scholar, covering publications from 2015 to 2025. The research process involved the stages of identification, selection, evaluation, and synthesis of literature relevant to the research topic. The results of the study indicate that the implementation of religious-humanistic leadership plays a crucial role in fostering positive student character through the integration of religious, humanistic, and moral values into school culture, the learning process, religious activities, and social interactions within the educational environment. This integration helps create a harmonious, inclusive school environment focused on strengthening students’ character.